Validation of Chinese version of the familiar tools use test for assessing limb apraxia in stroke patients - Wang, Jinni; Wei, Jingxin; Chen, Meilian; Gao, Lu; Liao, Xiaoyan (Frontiers in Neurology, 2025)
ObjectiveTo validate the Familiar Tools Use Test (FTT) of the Diagnostic Instrument for Limb Apraxia-Short Version in Chinese stroke patients.MethodsParticipants were conveniently enrolled from a neurology ward in a tertiary hospital in Guangzhou, China, between April 2023 and September 2023. Internal consistency, test–retest reliability, inter-rater reliability, dimensionality, convergent validity, and divergent validity were examined.ResultsIn total, 110 ischemic stroke patients were included. The FTT demonstrated satisfactory internal consistency (Cronbach’s α = 0.70–0.75), test–retest reliability (ICC 0.88–0.99, 95%CI), and inter-rater reliability (Kappa coefficients ranging from 0.83 to 1.00, p < 0.001). Exploratory factor analysis extracted one common factor for tool selection and two common factors for action execution. There were mild to moderate correlations between the scores of the FTT scales and the MoCA (ρ ranged from 0.37 to 0.50), indicating satisfactory convergent and divergent validity. The moderate correlations between the scores of the FTT scales and the PTU (ρ ranged from 0.49 to 0.51), indicating satisfactory concurrent validity. The prevalence of limb apraxia in patients with left brain damage when selecting, producing, and executing familiar tools were 14.9, 8.5, and 8.5%, respectively. While, the prevalence of apraxia during similar tasks in those with right brain damage were 3.0, 0, and 0%, respectively.ConclusionThe FTT was reliable and valid for assessing limb apraxia among Chinese ischemic stroke patients.